Factors Contributing to Incomplete of Manual and Electronic Medical Record (EMR) Entries in Hospital - Nasution, Nurlia Susanti; Alfiansyah, Gamasiano; Deharja, Atma; Suyoso, Gandu Eko Julianto (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: A complete medical record is defined as one that is fully completed by Healthcare Professionals (HCPs) within ≤ 24 hours after the patient is discharged. In the third quarter of 2022, X Regional Hospital recorded the highest percentage of incomplete inpatient medical records in October, totaling 465 incomplete records (32.68%). This study aims to analyze the factors contributing to the incompleteness of inpatient medical record documentation at the hospital using Lawrence Green's behavioral theory, focusing on predisposing, enabling, and reinforcing factors.Methods: This qualitative study employed data collection techniques such as observation, documentation, and interviews to nine informants, comprising one head of the medical records department, four attending physicians, three nurses, and one head of the inpatient ward. The data were analyzed through data reduction, data presentation, and conclusion drawing, followed by providing improvement recommendations.Results: The findings indicate predisposing factors include limited staff knowledge about medical record documentation. Enabling factors involve an insufficient number of computers, incomplete training attendance, and unawareness of Standard Operating Procedures (SOP) on medical record completeness. Reinforcing factors include the absence of punishment for non-compliance.Conclusion: Improvement efforts include conducting regular socialization, monitoring, and evaluation of SOP implementation for medical record completeness; proposing additional computers; organizing seminars and training on medical record documentation for medical record staff and HCPs; and implementing a reward and punishment system to enhance HCP performance in completing inpatient medical records.